Use of reconstructed 3D equilibria to determine onset conditions of helical cores in tokamaks for extrapolation to ITER. (15th January 2018) - Wingen, A.; Wilcox, R.S.; Seal, S.K.; Unterberg, E.A.; Cianciosa, M.R.; Delgado-Aparicio, L.F.; Hirshman, S.P.; Lao, L.L.
Abstract: Large, spontaneous m / n = 1/1 helical cores are shown to be expected in tokamaks such as ITER with extended regions of low- or reversed- magnetic shear profiles and q near 1 in the core. The threshold for this spontaneous symmetry breaking is determined using VMEC scans, beginning with reconstructed 3D equilibria from DIII-D and Alcator C-Mod based on observed internal 3D deformations. The helical core is a saturated internal kink mode (Wesson 1986 Plasma Phys. Control. Fusion 28 243); its onset threshold is shown to be proportional to ( d p / d ρ ) / B t 2 around q = 1. Below the threshold, applied 3D fields can drive a helical core to finite size, as in DIII-D. The helical core size thereby depends on the magnitude of the applied perturbation. Above it, a small, random 3D kick causes a bifurcation from axisymmetry and excites a spontaneous helical core, which is independent of the kick size. Systematic scans of the q-profile show that the onset threshold is very sensitive to the q-shear in the core. Helical cores occur frequently in Alcator C-Mod during ramp-up when slow current penetration results in a reversed shear q-profile, which is favorable for helical core formation. Finally, a comparison of the helical core onset threshold for discharges from DIII-D, Alcator C-Mod and ITER confirms that while DIII-D is marginally stable, Alcator C-Mod and especially ITER are highly susceptible to helical core formation without being driven by an externally applied 3D magnetic field.